PENDAMPINGAN KELOMPOK TERNAK BRAJAGAMA, TAMANTIRTO, KASIHAN, BANTUL, YOGYAKARTA DALAM MANAJEMEN PETERNAKAN TERPADU - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Integrated animal farming management system has been disseminated at animal farming group Brajagama, Tamantirto, Kasihan, Bantul. The purpose of the activity was to enhance the skill of the farmer especially on animal precopulatory behavior detection, planting and processing of green fodder, animal waste processing, recording and improvement of the farm-animal stall. This activity used the Focus Group Discussion (FGD) method to deliver the program. At the end of the program, it was shown that the farmers skill on animal precopulatory behavior detection were improved, more green fodder was available, the farmers could produce organic fertilizer from their animal waste and the farmers knowledge on animal farming management in general was better.